2022
DOI: 10.1002/adfm.202111610
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Design of Inflatable Soft Membranes Through Machine Learning

Abstract: Across fields of science, researchers have increasingly focused on designing soft devices that can shape-morph to achieve functionality. However, identifying a rest shape that leads to a target 3D shape upon actuation is a nontrivial task that involves inverse design capabilities. In this study, a simple and efficient platform is presented to design pre-programmed 3D shapes starting from 2D planar composite membranes. By training neural networks with a small set of finite element simulations, the authors are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Optimization problems can be solved by using different approaches such as the optimality criteria (OC) method [33,36], the sequential linear/integer programming method [33,39], the method of moving asymptotes [40], and the non-gradient method [41][42][43]. These methods have been used in diverse fields of, for example, additive manufacturing [44,45], metamaterials [46][47][48][49], bionics [32,48,50,51], medical devices [52], flexible electronics [53], soft robotics [54,55] and aerospace [22,27,56].…”
Section: Methodsmentioning
confidence: 99%
“…Optimization problems can be solved by using different approaches such as the optimality criteria (OC) method [33,36], the sequential linear/integer programming method [33,39], the method of moving asymptotes [40], and the non-gradient method [41][42][43]. These methods have been used in diverse fields of, for example, additive manufacturing [44,45], metamaterials [46][47][48][49], bionics [32,48,50,51], medical devices [52], flexible electronics [53], soft robotics [54,55] and aerospace [22,27,56].…”
Section: Methodsmentioning
confidence: 99%
“…Morin et al [17] found that the distribution of materials resulted in a high degree of freedom of programmability of the expansion or collapse pattern in their research of elastic cubes made of two soft materials with different stiffness (i.e., Ecoflex and PDMS). Using the same combination of materials, Forte et al [18] recently proposed a machine learning-based framework for the inverse design of the soft membrane that can achieve the pre-programmed deformation under inflation. Dammer et al [5] demonstrated a 3D-printable linear actuator and optimized the geometry parameters to extend its lifetime by considering the maximal strain.…”
Section: B Designing the Mechanical Properties Of Soft Robotsmentioning
confidence: 99%
“…To realize shape-morphing and complex curvature conforming of flat sheets, two strategies have been commonly pursued. One is to introduce inhomogeneous in-plane strains in soft stretchable materials via approaches such as pneumatic inflation ( 1 – 5 ), swelling ( 6 – 9 ), application of electric fields ( 10 , 11 ), and thermal activation ( 12 , 13 ). The other exploits kirigami and origami strategies to program the Gaussian curvatures from inextensible flat sheets ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%